Phosphate solubilizing bacteria inducing systemic resistance with a potential for use as biofertilizer for rice - Purwaningsih Purwaningsih; Siti Hadijah; Setia Budi; Sri Rahayu (STKIP Persada Khatulistiwa Sintang, 2023)
Induced systemic resistance (ISR) and biofertilizer are two activities in plant protection from pathogens as well as an alternative to the use of traditional fertilizers. The purpose of the study was to determine other features of 4 bacteria that have the ability as phosphate solvents and produce indole and siderophore compounds that determine them as inducers of systemic resistance and indicate their possibility to be applied as biofertilizers in rice plants. This study is experimental with four (4) bacteria that have been identified and characterized molecularly: Paenibacillus alvei AP4SR, Paenibacillus alvei AP6SR, Bacillus cereus RH8SR, and Bacillus cereus RH10SR. The results showed that the characteristics of the four bacteria could be applied as biofertilizers. The ability to fix nitrogen was shown by Paenibacillus alvei AP4SR, Paenibacillus alvei AP6SR and Bacillus cereus RH10SR, while the ability to dissolve potassium was shown by Paenibacillus alvei AP4SR, Bacillus cereus RH8SR, and Bacillus cereus RH10SR. Only three isolates were able to increase plant metabolite levels, namely Paenibacillus alvei AP4SR, Bacillus cereus RH10SR and Bacillus cereus RH8SR. Bacterial inoculation had a significant effect on plant height and the number of tillers at the age of 40 days, the number of tillers/plant increased to 56.52%..